Digital forensic science approach by file recovery research - Jo, Woo Yeon; Chang, Hyunsoo; Shon, Taeshik (Journal of Supercomputing, 2018)
Although many studies have been conducted on digital forensics, their viewpoints keep changing, and new studies are continuously required on fields that have not been researched yet. This paper proposes a privacy protection measure by applying permanent deletion to the Internet-of-Things platform: a digital forensic technique regarding privacy protection that has been regarded as a cautious subject. In addition, we propose a file recovery method by analyzing a file allocation area in a UNIX file system, which has not been addressed, and identifying the clue for journal area using a magic number.
Keywords: File allocation; File recovery; File systems; Forensic Techniques; Magic numbers; New study; Permanent deletion; Privacy protection; Digital forensics; IoT; Magic number; Permanent deletion; Recovery; UFS